2021
DOI: 10.2196/22693
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Ecological Momentary Assessment and Intervention and Health Behavior Change Among Adults in Rakai, Uganda: Pilot Randomized Controlled Trial

Abstract: Background An extraordinary increase in mobile phone ownership has revolutionized the opportunities to use mobile health approaches in lower- and middle-income countries (LMICs). Ecological momentary assessment and intervention (EMAI) uses mobile technology to gather data and deliver timely, personalized behavior change interventions in an individual’s natural setting. To our knowledge, there have been no previous trials of EMAI in sub-Saharan Africa. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The study was an assessment of the feasibility and acceptability of using mobile smartphones to implement EMAI in a prospective, parallel group, randomized pilot trial in Rakai, Uganda [15]. The trial purposively sampled adult participants (18-49 years) from the Rakai Community Cohort Study (RCCS), an open, population-based HIV and health surveillance cohort established in 1994 [16,17].…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was an assessment of the feasibility and acceptability of using mobile smartphones to implement EMAI in a prospective, parallel group, randomized pilot trial in Rakai, Uganda [15]. The trial purposively sampled adult participants (18-49 years) from the Rakai Community Cohort Study (RCCS), an open, population-based HIV and health surveillance cohort established in 1994 [16,17].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Due to unforeseen resource limitations, the study recruited approximately half the number expected in the study protocol. However, purposeful sampling ensured inclusion of the desired range of participant characteristics in the pilot trial [15]. Participants were informed of the study and, if they agreed to participate, were then contacted in-person and enrolled, contingent on their written voluntary informed consent.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot trial using EMA messaging to influence certain health-related behaviors was conducted in Rakai, Uganda in 2017 [ 9 ]. In addition to supporting healthful behaviors (eg, fruit and vegetable consumption), an EMA app sent real-time messages to support users in reducing smoking, drinking alcoholic beverages, and having condomless sex with a non-long-term partner.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, 35 full-text articles were included in this review. Several relevant protocol [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], baseline or pilot [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], and feasibility studies [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] were identified; however, they did not meet the inclusion criteria because trial outcomes were the focus of this review.…”
Section: Methodsmentioning
confidence: 99%